PATIENT COMPLIANCE AS AN EFFECTIVENESS FACTOR OF COMPLICATED DENDRITIC HERPETIC KERATITIS TREATMENT - D. Pavlenko (Bogomolets National Medical University, 2015)
Summary. Every year almost 10 million patients are registered with ophthalmic herpes. Herpetic keratitis is associated with more than 66,8% of the entire cornea pathology, 55,1% of all ulcerative lesions and it causes more than 60% of the corneal blindness, the recurrence rates in 20-75%. The most common pathogen of the herpetic keratitis is the herpes simplex virus - it is revealed in 50% of adults and 70-80% of children.Quite often, successful drug treatment of diseases depends not only on the proper doctor's prescription drugs, but also on the patient's compliance. According to the World Health Organization, about half of chronic patients do not fully comply with medical prescriptions and recommendations, about 50% of patients discontinue therapy within 6 months from the beginning, and only 15% continue treatment for a year. Now the main links of etiopathogenesis, clinical features are studied and treatment regimens of herpetic keratitis are developed, but the role of compliance of the patient during the disease is poorly studied. In this clinical case of recurrent herpetic keratitis flow tree shows the important role of compliance as a factor in the effectiveness of treatment of the patient. The patient was hospitalizes with of the recurrent course of superficial epithelial dendritic herpetic keratitis. Reduction of compliance of the patient led to the complicated course of the disease in the form of rerecurrence with ulceration of the cornea. Due to the combined treatment and awareness of compliance we were able to stabilize the herpetic keratitis and prevent complications.Therefore, while prescribing complex treatment attention must be payed to the observance of the patient's compliance. Increased compliance is one of the effectiveness factors, which allows achieving a more favorable course, reducing the terms of treatment, decrease and preventing complications, relapses and the need of re-hospitalization.